2020
DOI: 10.3390/ani10020345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobial Peptide Microcin J25 on Growth Performance, Immune Regulation, and Intestinal Microbiota in Broiler Chickens Challenged with Escherichia coli and Salmonella

Abstract: The purpose of this study was to investigate the effects of antimicrobial peptide microcin J25 (MccJ25) on growth performance, immune regulation, and intestinal microbiota in broilers. A total of 3120 one-day-old male Arbor Acres (AA) broilers were randomly allocated to five groups (12 replicates, 52 chickens per replicate). The treatments were control, challenge (0 mg/kg MccJ25), different dosages of antimicrobial peptide (AMP) (0.5 and 1mg/kg MccJ25), and antibiotic groups (20 mg/kg colistin sulfate). The Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…To achieve our final goal that is paving the way for further studies evaluating the potential of using MccJ25 as an alternative to antibiotics in livestock, the main objective of the present study was to assess the stability and inhibitory activity of MccJ25 under the physiological conditions encountered in the swine colon. Although in vivo studies conducted in mice or in model livestock animals (Forkus et al, 2017;Yu et al, 2017;Wang et al, 2020) have shown the potential of this bacteriocin as an alternative to antibiotics, and its high stability in the upper part of the GI tract has been assessed (Naimi et al, 2018), it was necessary to specifically determine the efficiency of MccJ25 against a major pathogen, such as Salmonella Newport, in conditions mimicking those found in the swine colon. We showed here that the potent MccJ25 inhibitory activity against Salmonella Newport measured in LB broth is maintained in the conditions used to mimic the physiological conditions encountered in the swine colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve our final goal that is paving the way for further studies evaluating the potential of using MccJ25 as an alternative to antibiotics in livestock, the main objective of the present study was to assess the stability and inhibitory activity of MccJ25 under the physiological conditions encountered in the swine colon. Although in vivo studies conducted in mice or in model livestock animals (Forkus et al, 2017;Yu et al, 2017;Wang et al, 2020) have shown the potential of this bacteriocin as an alternative to antibiotics, and its high stability in the upper part of the GI tract has been assessed (Naimi et al, 2018), it was necessary to specifically determine the efficiency of MccJ25 against a major pathogen, such as Salmonella Newport, in conditions mimicking those found in the swine colon. We showed here that the potent MccJ25 inhibitory activity against Salmonella Newport measured in LB broth is maintained in the conditions used to mimic the physiological conditions encountered in the swine colon.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, therapeutic administration of MccJ25 attenuated enterotoxigenic Escherichia coli (ETEC) clinical symptoms in a mouse model of intestinal inflammation and showed a reduction of the intestinal pathogen colonization and a decrease of inflammation (Yu et al, 2020). Administration of MccJ25 to poultry or weaned pigs, either via a probiotic strain engineered to produce MccJ25 (Forkus et al, 2017), or via diet supplementation by MccJ25 (Yu et al, 2017;Wang et al, 2020), was shown to effectively reduce S. enteritidis carriage (Forkus et al, 2017), or improve growth performance and gut health (Yu et al, 2017;Wang et al, 2020). However, very little information is available on the stability and activity of MccJ25 under the conditions encountered specifically in the human or animal gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Timbermont et al [ 140 ] demonstrated the ability of perfrin, i.e., a bacteriocin expressing the NetB toxin that is produced by C. perfringens , to inhibit the growth of C. perfringens isolated from necrotic enteritis in poultry. In an in-vivo study, Wang et al [ 141 ] confirmed the possibility of using microcin as a substitute for antibiotics in the poultry industry as this bacteriocin reduced the number of anaerobic bacteria and limited the frequency of Salmonella infections. Svetoch et al [ 142 ] showed a reducing effect on Campylobacter jejuni in chicks that were infected experimentally with enterocin produced by Bacillus polymyxa .…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…MccJ25 has been shown to decrease S. enterica counts in the liver and spleen in mice (Lopez et al, 2007) and in the gastrointestinal tract of turkeys (Forkus et al, 2017), and to relieve diarrhea and systematic inflammation in weaned pigs (Yu et al, 2017). Furthermore, MccJ25 was shown to improve performance, fecal microbiota composition and systematic inflammation of broilers (Wang et al, 2020). Further studies are needed however to validate the potential of microcins as therapeutic agents in human or veterinary medicine.…”
Section: Potential Applications Of Microcins and Future Prospectmentioning
confidence: 99%
“…Moreover, absence of immunomodulatory effect and toxicity of MccJ25 was observed at the therapeutic dose (9 mg/kg), much higher doses only (18 mg/kg) being able to cause a low toxicity ( Yu et al, 2018b ). Furthermore, MccJ25 also decreases the serum concentration levels of the pro-inflammatory cytokines IL-6, IL-1β, and TNF-α, together with an increase in anti-inflammatory IL-10 in weaned pigs ( Wang et al, 2020 ) and in broiler chicken ( Yu et al, 2017 ) fed with MccJ25-supplemented diet. Taken together, these in vivo studies conducted in different animal models indicate that MccJ25 diet supplementation can lower inflammation together with affording protection against pathogens, providing interesting perspectives in inflammatory intestinal diseases.…”
Section: Microcins and The Immune Systemmentioning
confidence: 99%